Kinerja E-Commerce Toko Tani Indonesia dalam Pengembangan Distribusi Pangan - Anugrah, Iwan Setiajie; Hestina, Juni; Suryani, Erma; Wahyuni, Sri; Hermanto (Analisis Kebijakan Pertanian, 2025)
E-Commerce is an innovation that is applied in the management of Toko Tani Indonesia (TTI) or Indonesian Farmer Shops started in 2018 by the Food Security Agency (BKP), Ministry of Agriculture. This technology is used to support the provision of information on the availability of commodity supplies to TTI and stocks in each Community Food Business Development as TTI's partner in food procurement. This paper aimed to analyze the performance of e-commerce in TTI activities and identify opportunities and constraints of using this application to support TTI sustainability. The study used a qualitative descriptive analysis method. The result of this study concluded that the e-commerce application can improve TTI performance to make food availability easier and cheaper for consumers due to less distribution costs by cutting some distribution channels.  By utilizing e-commerce, BKP has developed TTI to become a distribution centre for strategic food as well as an instrument for food price stabilization. However, the implementation of e-commerce in TTI operation encounters several constraints, such as the ability of operators to utilize this technology, unstable signals and networks, and the ability of farmers to use the features of e-commerce gadgets. This study recommended the need for technical guidance on e-commerce system applications for farmers, operators, and vendors, to buyers. In addition, support from various parties related to online distribution services is still needed to develop TTI massively as an alternative place for meeting people's food needs online
Keywords: e-commerce; food distribution; food price commodities; indonesian farmer shop